Wrinkle-proof and antistatic polyester fabric and preparation method thereof

By using end-alkenyl modified hyperbranched polyester/nanosilver composite materials and quaternary ammonium salt-type surfactants in polyester fabrics, and immersion treatment, the problems of electrostatic and dust adsorption of polyester fabrics are solved, and excellent antistatic, antibacterial and wrinkle-proof properties are achieved.

CN119372927BActive Publication Date: 2025-03-14CHANGXINGQUANNENG TEXTILE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411922109.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-14
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

During actual use, existing polyester fabrics are prone to static electricity and adsorbing dust, resulting in accumulation of static charge and affecting the performance of taking.

Method used

Using end-alkenyl modified hyperbranched polyester/nanosilver composite materials, quaternary ammonium surfactants and methoxy polyethylene glycol acrylate, antistatic agents are prepared through polymerization, and combined with water to form an antistatic finishing solution, immersed in polyester fiber fabric to form a conductive layer to improve antistatic properties.

Benefits of technology

It significantly improves the anti-static and antibacterial properties of polyester fabrics, while improving the anti-wrinkle effect and water-resistant performance of the fabrics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372927B_ABST
    Figure CN119372927B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of multi-layer composite fabrics, and discloses an anti-wrinkle antistatic polyester fabric and a preparation method thereof. The preparation method comprises: performing polymerization reaction on terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, quaternary ammonium salt type surfactant, and methoxy polyethylene glycol acrylate under initiator conditions to obtain an antistatic agent, impregnating a single-layer polyester fabric with an antistatic finishing liquid obtained by compounding the antistatic agent and water, respectively obtaining a surface layer fabric and an inner layer fabric, and compounding to obtain an anti-wrinkle antistatic polyester fabric. The polyester fabric has excellent antistatic performance, good antibacterial performance, and good anti-wrinkle effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of multi-layer composite fabrics, and in particular to an anti-wrinkle and anti-static polyester fabric and a preparation method thereof. Background Art

[0002] In recent years, the wrinkle resistance and wrinkle-free properties of fabrics have become a hot topic in the field of clothing wearability research. The wrinkle resistance of fabrics can also be called crumpling resistance, which refers to the property of forming wrinkles by plastic bending deformation when rubbing the fabric. The wrinkle resistance of fabrics is also called the anti-wrinkle property of fabrics, which generally refers to the wrinkle recovery ability of fabrics. Polyester fiber fabrics have the advantages of excellent elasticity, shape retention, washability, etc., and excellent anti-wrinkle performance, but they also have obvious disadvantages. Since polyester fiber is a hydrophobic fiber with poor conductivity and low moisture absorption rate, it is easy to generate static electricity and adsorb dust, causing static charge accumulation. Therefore, polyester fiber fabrics often bring many inconveniences due to the generation of static electricity during actual wearing.

[0003] Prior art such as Chinese patent CN108943901A discloses an antistatic and anti-wrinkle fabric, which is made by compounding a base layer containing polyester fiber, conductive fiber and plant fiber with an intermediate layer and a shape memory polyurethane microporous membrane as an anti-wrinkle layer to give the composite fabric antistatic and anti-wrinkle and wear-resistant effects. However, the antistatic property of the fabric is given by the conductive fiber, and the anti-wrinkle property of the fabric is only determined by the anti-wrinkle layer. The antibacterial and moisture absorption properties of the fabric need to be improved. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an anti-wrinkle and anti-static polyester fabric and a preparation method thereof. The polyester fabric has excellent anti-static performance, good antibacterial performance and good anti-wrinkle effect.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing an anti-wrinkle and antistatic polyester fabric comprises the following steps:

[0007] Step (1), mixing terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile, reacting, cooling, rotary evaporating, washing, and drying after the reaction to obtain an antistatic agent; mixing the antistatic agent with water to obtain an antistatic finishing liquid;

[0008] The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps:

[0009] S11, mixing γ-(2,3-epoxypropoxy)propyltrimethoxysilane with an ethanol aqueous solution, adding a regulator to adjust the pH value, adding nanosilver, reacting, and after the reaction is completed, filtering, washing, and drying to obtain epoxidized nanosilver;

[0010] S12, dissolving the terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide, adding p-toluenesulfonic acid, dropping acrylic acid, reacting after the dropping is complete, cooling after the reaction is complete, adding boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver, continuing the reaction, and rotary evaporating to obtain a terminal olefin-modified hyperbranched polyester / nanosilver composite material;

[0011] The quaternary ammonium salt surfactant is prepared by the following steps:

[0012] The dimethylaminoethyl methacrylate and acetone are uniformly mixed, 1,12-dibromododecane is added dropwise, and after the addition is complete, the mixture is reacted. After the reaction is complete, the mixture is filtered, recrystallized, and dried to obtain a quaternary ammonium salt surfactant;

[0013] Step (2), spinning polyester fibers into yarns as warp yarns and weft yarns, weaving to obtain a single-layer polyester fabric; impregnating the single-layer polyester fabric with an antistatic finishing liquid, and after the impregnation, drying and baking to obtain a surface fabric and an inner fabric respectively;

[0014] Wherein, the polyester fiber is prepared by the following steps:

[0015] The polyester chips are mixed with the normal pressure dyeable polyester masterbatch, melt extruded, spun, cooled, and drawn to obtain polyester fibers;

[0016] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning them, and sewing the surface fabric and the inner fabric by a multi-layer fabric quilting machine to obtain an anti-wrinkle and antistatic polyester fabric.

[0017] Preferably, in step (1), the mass ratio of the terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile is 20-25:6.5-7:18-20:5-6:100-120:0.4-0.5; the reaction conditions are: reaction at a speed of 180-230 r / min and a temperature of 70-80° C. for 6-8 hours; and the mass ratio of the antistatic agent to water is 1:20-25.

[0018] Preferably, when preparing the terminal olefin modified hyperbranched polyester / nanosilver composite material in step (1), in S11: the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50wt% ethanol aqueous solution, and nanosilver is 0.8-1:200-220:10, and the ethanol aqueous solution is 50wt% ethanol aqueous solution; the reaction conditions are: reacting at a pH value of 4-5 and a temperature of 45-55°C for 4-5h.

[0019] Preferably, the regulator comprises a 1 mol / L hydrogen chloride aqueous solution.

[0020] Preferably, when preparing the terminal olefin modified hyperbranched polyester / nanosilver composite material in step (1), in S12: the mass ratio of terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 21-25:100-120:1-1.1:2.8-3:1.2-1.5:9-11:15-18; the dripping condition of acrylic acid is: dripping at a temperature of 100-110°C for 1.5-2h; the reaction condition is: reacting at a temperature of 100-105°C for 4-5h in a nitrogen atmosphere; and the continued reaction condition is: continuing the reaction at a temperature of 45-55°C for 24-28h.

[0021] Preferably, when preparing the quaternary ammonium salt surfactant in step (1), the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane is 2.1-2.4:1; the dripping time of 1,12-dibromododecane is 20-30 min; and the reaction conditions are: reacting at a set temperature of 60-70° C. for 8-10 h.

[0022] Preferably, in step (2), the yarn counts of the warp and weft yarns are both 40-60S in British standard; the weight of the single-layer polyester fabric is 180-200 g / m 2 The dipping operation includes: dipping at 40-50°C for 50-60 minutes, a bath ratio of 20-30:1, two dippings and two rollings, and a rolling rate of 88-94%; the drying condition is: drying at 80-90°C for 3-5 minutes; the baking condition is: baking at 140-150°C for 2-3 minutes.

[0023] Preferably, when preparing the polyester fiber in step (2), the mass ratio of the polyester chips to the normal pressure dyeable polyester masterbatch is 100:26-30; the melt extrusion conditions are: melt extrusion through a twin-screw melt spinning machine, the temperature is 265-275°C in zone 1, 275-280°C in zone 2, 278-290°C in zone 3, and 280-290°C in zone 4; the spinning speed is 800-1000 m / min; the drafting multiple is 3-3.6 times; and the linear density of the polyester fiber is 180-200 dtex.

[0024] Preferably, an anti-wrinkle and anti-static polyester fabric is prepared by the method for preparing the anti-wrinkle and anti-static polyester fabric as described above.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The invention prepares a terminal olefin modified hyperbranched polyester / nanosilver composite material containing a quaternary ammonium salt structure and an acrylate group, and polymerizes it with a hydrophilic component hydroxyethyl methacrylate, a quaternary ammonium salt type surfactant containing a cationic group, and a methoxy polyethylene glycol acrylate containing a polyether hydrophilic structure under an initiator condition to obtain an antistatic agent with antibacterial and antistatic properties; a polyester fiber added with a normal pressure dyeable polyester masterbatch is made into a single-layer polyester fabric, and then impregnated with an antistatic finishing liquid obtained by compounding the antistatic agent and water to obtain a surface fabric and an inner fabric respectively, and after compounding, an anti-wrinkle antistatic polyester fabric is obtained. The polyester fabric has excellent antistatic properties, good antibacterial properties, and good anti-wrinkle effect.

[0027] The invention introduces an acrylate structure containing a carbon-carbon double bond by subjecting part of the terminal hydroxyl groups of a hydroxyl-terminated hyperbranched polyester to an esterification reaction with the carboxyl group of acrylic acid under the catalytic condition of p-toluenesulfonic acid, and then adds 2,3-epoxypropyltrimethylammonium chloride and epoxysilane coupling agent-modified epoxidized nano-silver after the reaction is completed, and reacts the epoxidized nano-silver with the remaining terminal hydroxyl groups of the hydroxyl-terminated hyperbranched polyester under the condition of boron trifluoride etherate to obtain a terminal olefin-modified hyperbranched polyester / nano-silver composite material containing a quaternary ammonium salt structure and an acrylate group.

[0028] The invention conducts a quaternization reaction on dimethylaminoethyl methacrylate and 1,12-dibromododecane to obtain a quaternary ammonium salt type surfactant with a diquaternary ammonium salt cationic structure, and copolymerizes the quaternary ammonium salt with a terminal olefin modified hyperbranched polyester / nanosilver composite material by using a carbon-carbon double bond and a hydrophilic component hydroxyethyl methacrylate and a methoxy polyethylene glycol acrylate containing a polyether hydrophilic structure under an initiator condition, and the obtained antistatic agent is compounded with water to obtain an antistatic finishing liquid;

[0029] Among them, the quaternary ammonium salt surfactant contained in the antistatic agent and the terminal olefin modified hyperbranched polyester / nano-silver composite material both contain quaternary ammonium salt cationic groups. During the padding process of the polyester fabric, this polar group can form a conductive layer on the fabric, and combine with the moisture in the air to reduce the resistance of the polyester fabric, accelerate the dissipation of static charge, and synergistically improve the antistatic performance of the polyester fabric with the hydrophilic component hydroxyethyl methacrylate and methoxy polyethylene glycol acrylate containing a polyether hydrophilic structure; at the same time, the quaternary ammonium salt group has antibacterial activity, and can synergistically improve the antibacterial performance of the polyester fabric with the inorganic antibacterial agent nano-silver;

[0030] The present invention prepares a single-layer polyester fabric by adding polyester fiber to which normal pressure dyeable polyester masterbatch is added, and then immerses and rolls an antistatic finishing liquid obtained by compounding an antistatic agent and water to obtain a surface layer fabric and an inner layer fabric respectively, and after compounding, an anti-wrinkle antistatic polyester fabric is obtained;

[0031] Among them, the normal pressure dyeable polyester masterbatch is a normal pressure cationic dyeable polyester ECDP containing a polyether hydrophilic segment and a sulfonate anion group. When added to polyester chips, sulfonate anion groups can be introduced into polyester fibers to improve the moisture absorption and regain and antistatic properties of polyester fabrics. The antistatic finishing liquid contains ester groups and quaternary ammonium salt cationic groups. During the padding process, the ester groups can produce eutectics with the polyester fibers based on the principle of similar compatibility. Ionic crosslinking occurs between the quaternary ammonium salt cationic groups and the sulfonate anion groups in the polyester fabric to form ionic bonds, which strengthens the interaction between the fiber molecular chains in the polyester fabric, which not only improves the wash resistance of the polyester fabric, but also because the antistatic agent is deposited between the fibers of the polyester fabric using ionic bonds, it limits the deformation and movement of the polyester fibers and improves the wrinkle resistance of the polyester fabric. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a process flow chart for preparing wrinkle-resistant and antistatic polyester fabrics in the present invention;

[0033] Figure 2 It is a schematic structural diagram of the wrinkle-resistant and antistatic polyester fabric prepared in the present invention;

[0034] Figure 3 It is a bar graph of the antibacterial rate of polyester fabrics prepared in the embodiments and comparative examples of the present invention in the performance test;

[0035] Figure 4 It is a histogram of surface resistance in the performance test of polyester fabrics prepared in the embodiments and comparative examples of the present invention;

[0036] Figure 5 It is a histogram of the static voltage half-life in the performance test of the polyester fabric prepared in the embodiment and the comparative example of the present invention;

[0037] In the figure:

[0038] 1. Surface fabric; 2. Lining fabric. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0040] Embodiment 1:

[0041] like Figure 1-Figure 2 As shown, this embodiment discloses a method for preparing an anti-wrinkle and antistatic polyester fabric, comprising the following steps:

[0042] Step (1), mixing a terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, a quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile in a mass ratio of 20:6.5:18:5:100:0.4, reacting at a speed of 180 r / min and a temperature of 70° C. for 8 hours, cooling to room temperature after the reaction, and removing the solvent ethanol by rotary evaporation at a temperature of 60° C. to obtain a reaction product, adding toluene 5 times the mass of the reaction product for washing, and drying at a temperature of 80° C. for 30 hours to obtain an antistatic agent; mixing the antistatic agent with water in a mass ratio of 1:25 to obtain an antistatic finishing liquid;

[0043] The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps:

[0044] S11, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was mixed with 50 wt% ethanol aqueous solution, 1 mol / L hydrogen chloride aqueous solution was added dropwise to adjust the pH value to 4, nanosilver was added, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50 wt% ethanol aqueous solution and nanosilver was 0.8:200:10, and the reaction was carried out at 45°C for 5 hours. After the reaction was completed, the filter cake was taken out by suction, 6 times the mass of ethanol of the filter cake was added for washing, and the nanosilver was dried at 50°C for 26 hours to obtain epoxidized nanosilver;

[0045] S12, dissolving the terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide, adding p-toluenesulfonic acid, dripping acrylic acid at 100°C for 2 hours, reacting at 100°C for 5 hours in a nitrogen atmosphere after the addition is complete, cooling after the reaction is complete, adding boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver, and continuing the reaction at 45°C for 28 hours, and after the reaction is complete, removing the solvent N,N-dimethylformamide by rotary evaporation at 100°C to obtain a terminal olefin-modified hyperbranched polyester / nanosilver composite material;

[0046] The mass ratio of the terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride ethyl etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 21:100:1:2.8:1.2:9:15;

[0047] The quaternary ammonium salt surfactant is prepared by the following steps:

[0048] Dimethylaminoethyl methacrylate and acetone were mixed uniformly at a mass ratio of 1:40, 1,12-dibromododecane was added dropwise, the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane was 2.1:1, the dropping time was 20 min, after the dropping was completed, the reaction was carried out at a set temperature of 60°C for 10 h, after the reaction was completed, the filter cake was taken out by suction, ethanol 8 times the mass of the filter cake was added for recrystallization three times, and the mixture was dried at 50°C for 24 h to obtain a quaternary ammonium surfactant;

[0049] Step (2), spinning polyester fiber into yarn as warp and weft yarn, the yarn count is 40S in British standard, weaving, and obtaining a gram weight of 180 g / m 2 The single-layer polyester fabric is impregnated with an antistatic finishing liquid at a bath ratio of 20:1, and is impregnated at 40°C for 60 minutes, and is double-impregnated and double-rolled, with a rolling rate of 88%. After the impregnation, the fabric is dried at 80°C for 5 minutes, and baked at 140°C for 3 minutes to obtain a surface layer fabric and an inner layer fabric, respectively.

[0050] Wherein, the polyester fiber is prepared by the following steps:

[0051] The polyester chips and the normal pressure dyeable polyester masterbatch were mixed in a twin-screw extruder at a mass ratio of 100:26, and melt-extruded through a twin-screw melt spinning machine at a temperature of 265°C in the first zone, 275°C in the second zone, 278°C in the third zone, and 280°C in the fourth zone. The spinning was carried out at a spinning speed of 800 m / min, and the spinning was carried out, followed by cooling and drawing at a drawing multiple of 3 times to obtain a polyester fiber with a linear density of 200 dtex.

[0052] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning the layers, using polyester sewing thread as sewing thread, and sewing the surface fabric and the inner fabric through a multi-layer fabric quilting machine to obtain an anti-wrinkle and antistatic polyester fabric.

[0053] Embodiment 2:

[0054] This embodiment discloses a method for preparing an anti-wrinkle and antistatic polyester fabric, comprising the following steps:

[0055] Step (1), mixing a terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, a quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile in a mass ratio of 22:6.6:18.5:5.3:105:0.42, reacting at a speed of 200 r / min and a temperature of 75° C. for 7 hours, cooling to room temperature after the reaction, and removing the solvent ethanol by rotary evaporation at a temperature of 65° C. to obtain a reaction product, adding toluene 6 times the mass of the reaction product for washing, and drying at a temperature of 85° C. for 26 hours to obtain an antistatic agent; mixing the antistatic agent with water in a mass ratio of 1:24 to obtain an antistatic finishing liquid;

[0056] The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps:

[0057] S11, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was mixed with 50wt% ethanol aqueous solution, 1mol / L hydrogen chloride aqueous solution was added dropwise to adjust the pH value to 4.5, nanosilver was added, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50wt% ethanol aqueous solution and nanosilver was 0.85:205:10, and the mixture was reacted at 50°C for 4.5h. After the reaction was completed, the mixture was filtered, the filter cake was taken, 6 times the mass of the filter cake was added with ethanol for washing, and the mixture was dried at 55°C for 25h to obtain epoxidized nanosilver;

[0058] S12, dissolving the terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide, adding p-toluenesulfonic acid, dripping acrylic acid at 105°C for 2 hours, reacting at 105°C in a nitrogen atmosphere for 4.5 hours, cooling after the reaction, adding boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver, and continuing the reaction at 50°C for 26 hours, and after the reaction, removing the solvent N,N-dimethylformamide by rotary evaporation at 110°C to obtain a terminal olefin-modified hyperbranched polyester / nanosilver composite material;

[0059] The mass ratio of terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride ethyl etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 22:105:1:2.85:1.3:9.5:16;

[0060] The quaternary ammonium salt surfactant is prepared by the following steps:

[0061] Dimethylaminoethyl methacrylate and acetone were mixed uniformly at a mass ratio of 1:45, 1,12-dibromododecane was added dropwise, the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane was 2.2:1, the dropping time was 25 min, after the dropping was completed, the reaction was carried out at a set temperature of 65°C for 9 h, after the reaction was completed, the filter cake was taken out by suction, ethanol 8 times the mass of the filter cake was added for recrystallization three times, and the mixture was dried at 55°C for 22 h to obtain a quaternary ammonium surfactant;

[0062] Step (2), spinning polyester fiber into yarn as warp and weft yarn, the yarn count is 45S in British standard, and weaving to obtain a gram weight of 185g / m 2The single-layer polyester fabric is impregnated with an antistatic finishing liquid at a bath ratio of 25:1, and is impregnated at 45°C for 55 minutes, and is double-impregnated and double-rolled, with a rolling rate of 90%. After the impregnation, the fabric is dried at 85°C for 4 minutes, and baked at 145°C for 2.5 minutes to obtain a surface layer fabric and an inner layer fabric, respectively.

[0063] Wherein, the polyester fiber is prepared by the following steps:

[0064] The polyester chips and the normal pressure dyeable polyester masterbatch were mixed in a twin-screw extruder at a mass ratio of 100:27, and melt-extruded through a twin-screw melt spinning machine at a temperature of 265°C in the first zone, 275°C in the second zone, 283°C in the third zone, and 285°C in the fourth zone. The spinning was carried out at a spinning speed of 900 m / min, and the spinning was carried out. The spinning was cooled and drawn at a drawing multiple of 3.2 times to obtain a polyester fiber with a linear density of 195 dtex.

[0065] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning the layers, using polyester sewing thread as sewing thread, and sewing the surface fabric and the inner fabric through a multi-layer fabric quilting machine to obtain an anti-wrinkle and antistatic polyester fabric.

[0066] Embodiment 3:

[0067] This embodiment discloses a method for preparing an anti-wrinkle and antistatic polyester fabric, comprising the following steps:

[0068] Step (1), mixing a terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, a quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile in a mass ratio of 23:6.8:19:5.5:110:0.45, reacting at a speed of 200 r / min and a temperature of 75° C. for 7 hours, cooling to room temperature after the reaction, and removing the solvent ethanol by rotary evaporation at a temperature of 65° C. to obtain a reaction product, adding toluene 6 times the mass of the reaction product for washing, and drying at a temperature of 85° C. for 26 hours to obtain an antistatic agent; mixing the antistatic agent with water in a mass ratio of 1:23 to obtain an antistatic finishing liquid;

[0069] The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps:

[0070] S11, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was mixed with 50wt% ethanol aqueous solution, 1mol / L hydrogen chloride aqueous solution was added dropwise to adjust the pH value to 4.5, nanosilver was added, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50wt% ethanol aqueous solution and nanosilver was 0.9:210:10, and the mixture was reacted at 50°C for 4.5h. After the reaction was completed, the mixture was filtered, the filter cake was taken, 6 times the mass of the filter cake was added with ethanol for washing, and the mixture was dried at 55°C for 25h to obtain epoxidized nanosilver;

[0071] S12, dissolving the terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide, adding p-toluenesulfonic acid, dripping acrylic acid at 105°C for 2 hours, reacting at 105°C in a nitrogen atmosphere for 4.5 hours, cooling after the reaction, adding boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver, and continuing the reaction at 50°C for 26 hours, and after the reaction, removing the solvent N,N-dimethylformamide by rotary evaporation at 110°C to obtain a terminal olefin-modified hyperbranched polyester / nanosilver composite material;

[0072] The mass ratio of terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride ethyl etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 23:110:1:2.9:1.3:10:16.5;

[0073] The quaternary ammonium salt surfactant is prepared by the following steps:

[0074] Dimethylaminoethyl methacrylate and acetone were mixed uniformly at a mass ratio of 1:45, 1,12-dibromododecane was added dropwise, the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane was 2.25:1, the dropping time was 25 min, after the dropping was completed, the reaction was carried out at a set temperature of 65°C for 9 h, after the reaction was completed, the filter cake was taken out by suction, ethanol 8 times the mass of the filter cake was added for recrystallization three times, and the mixture was dried at 55°C for 22 h to obtain a quaternary ammonium surfactant;

[0075] Step (2), spinning polyester fiber into yarn as warp and weft yarn, the yarn count is 50S in British standard, and weaving to obtain a gram weight of 190g / m 2 The single-layer polyester fabric is impregnated with an antistatic finishing liquid at a bath ratio of 25:1, and is impregnated at 45°C for 55 minutes, and is double-impregnated and double-rolled, with a rolling rate of 90%. After the impregnation, the fabric is dried at 85°C for 4 minutes, and baked at 145°C for 2.5 minutes to obtain a surface layer fabric and an inner layer fabric, respectively.

[0076] Wherein, the polyester fiber is prepared by the following steps:

[0077] The polyester chips and the normal pressure dyeable polyester masterbatch were mixed in a twin-screw extruder at a mass ratio of 100:28, and melt-extruded through a twin-screw melt spinning machine at a temperature of 270°C in the first zone, 278°C in the second zone, 283°C in the third zone, and 285°C in the fourth zone. The spinning was carried out at a spinning speed of 900 m / min, and the spinning was carried out. The spinning was cooled and drawn at a drawing multiple of 3.3 times to obtain a polyester fiber with a linear density of 190 dtex.

[0078] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning the layers, using polyester sewing thread as sewing thread, and sewing the surface fabric and the inner fabric through a multi-layer fabric quilting machine to obtain an anti-wrinkle and antistatic polyester fabric.

[0079] Embodiment 4:

[0080] This embodiment discloses a method for preparing an anti-wrinkle and antistatic polyester fabric, comprising the following steps:

[0081] Step (1), mixing a terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, a quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile in a mass ratio of 24:6.9:19.5:5.8:115:0.48, reacting at a speed of 200 r / min and a temperature of 75° C. for 7 hours, cooling to room temperature after the reaction, and removing the solvent ethanol by rotary evaporation at a temperature of 65° C. to obtain a reaction product, adding toluene 6 times the mass of the reaction product for washing, and drying at a temperature of 85° C. for 26 hours to obtain an antistatic agent; mixing the antistatic agent with water in a mass ratio of 1:22 to obtain an antistatic finishing liquid;

[0082] The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps:

[0083] S11, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was mixed with 50wt% ethanol aqueous solution, 1mol / L hydrogen chloride aqueous solution was added dropwise to adjust the pH value to 4.5, nanosilver was added, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50wt% ethanol aqueous solution and nanosilver was 0.95:215:10, and the mixture was reacted at 50°C for 4.5h. After the reaction was completed, the mixture was filtered, the filter cake was taken, ethanol 6 times the mass of the filter cake was added for washing, and the mixture was dried at 55°C for 25h to obtain epoxidized nanosilver;

[0084] S12, dissolving the terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide, adding p-toluenesulfonic acid, dripping acrylic acid at 110°C for 2 hours, reacting at 105°C in a nitrogen atmosphere for 4.5 hours, cooling after the reaction, adding boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver, and continuing the reaction at 50°C for 26 hours, and after the reaction, removing the solvent N,N-dimethylformamide by rotary evaporation at 110°C to obtain a terminal olefin-modified hyperbranched polyester / nanosilver composite material;

[0085] The mass ratio of terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride ethyl etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 24:115:1:2.95:1.3:10.5:17;

[0086] The quaternary ammonium salt surfactant is prepared by the following steps:

[0087] Dimethylaminoethyl methacrylate and acetone were mixed uniformly at a mass ratio of 1:45, 1,12-dibromododecane was added dropwise, the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane was 2.3:1, the dropping time was 25 min, after the dropping was completed, the reaction was carried out at a set temperature of 65°C for 9 h, after the reaction was completed, the filter cake was taken out by suction, ethanol 8 times the mass of the filter cake was added for recrystallization three times, and the mixture was dried at 55°C for 22 h to obtain a quaternary ammonium surfactant;

[0088] Step (2), spinning polyester fiber into yarn as warp and weft yarn, the yarn count is 55S in British standard, and weaving to obtain a gram weight of 195g / m 2 The single-layer polyester fabric is impregnated with an antistatic finishing liquid at a bath ratio of 25:1, and is impregnated at 45°C for 55 minutes, and is double-impregnated and double-rolled, with a rolling rate of 90%. After the impregnation, the fabric is dried at 85°C for 4 minutes, and baked at 145°C for 2.5 minutes to obtain a surface layer fabric and an inner layer fabric, respectively.

[0089] Wherein, the polyester fiber is prepared by the following steps:

[0090] The polyester chips and the normal pressure dyeable polyester masterbatch were mixed in a twin-screw extruder at a mass ratio of 100:28, and melt-extruded through a twin-screw melt spinning machine at a temperature of 270°C in the first zone, 278°C in the second zone, 285°C in the third zone, and 290°C in the fourth zone. The spinning was performed at a spinning speed of 900 m / min, and the spinning was performed after cooling and drawing at a drawing multiple of 3.5 times to obtain a polyester fiber with a linear density of 185 dtex.

[0091] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning the layers, using polyester sewing thread as sewing thread, and sewing the surface fabric and the inner fabric through a multi-layer fabric quilting machine to obtain an anti-wrinkle and antistatic polyester fabric.

[0092] Embodiment 5:

[0093] This embodiment discloses a method for preparing an anti-wrinkle and antistatic polyester fabric, comprising the following steps:

[0094] Step (1), mixing a terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, a quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile in a mass ratio of 25:7:20:6:120:0.5, reacting at a speed of 230 r / min and a temperature of 80° C. for 6 hours, cooling to room temperature after the reaction, and removing the solvent ethanol by rotary evaporation at a temperature of 70° C. to obtain a reaction product, adding toluene 8 times the mass of the reaction product for washing, and drying at a temperature of 90° C. for 24 hours to obtain an antistatic agent; mixing the antistatic agent with water in a mass ratio of 1:20 to obtain an antistatic finishing liquid;

[0095] The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps:

[0096] S11, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was mixed with 50wt% ethanol aqueous solution, 1mol / L hydrogen chloride aqueous solution was added to adjust the pH value to 5, nanosilver was added, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50wt% ethanol aqueous solution and nanosilver was 1:220:10, and the mixture was reacted at 55°C for 4h. After the reaction was completed, the mixture was filtered, the filter cake was taken, 8 times the mass of the filter cake was added with ethanol for washing, and the mixture was dried at 60°C for 24h to obtain epoxidized nanosilver;

[0097] S12, dissolving the terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide, adding p-toluenesulfonic acid, dripping acrylic acid at 110°C for 1.5 hours, reacting at 105°C for 4 hours in a nitrogen atmosphere after the addition is complete, cooling after the reaction is complete, adding boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver, and continuing the reaction at 55°C for 24 hours, and after the reaction is complete, removing the solvent N,N-dimethylformamide by rotary evaporation at 120°C to obtain a terminal olefin-modified hyperbranched polyester / nanosilver composite material;

[0098] The mass ratio of terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride ethyl etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 25:120:1.1:3:1.5:11:18;

[0099] The quaternary ammonium salt surfactant is prepared by the following steps:

[0100] Dimethylaminoethyl methacrylate and acetone were mixed uniformly at a mass ratio of 1:50, 1,12-dibromododecane was added dropwise, the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane was 2.4:1, the dropping time was 30 min, after the dropping was completed, the reaction was carried out at a set temperature of 70°C for 8 h, after the reaction was completed, the filter cake was taken out by suction, ethanol 10 times the mass of the filter cake was added for recrystallization three times, and the mixture was dried at 60°C for 20 h to obtain a quaternary ammonium surfactant;

[0101] Step (2), spinning polyester fiber into yarn as warp and weft yarn, the yarn count is 60S in British standard, and weaving to obtain a gram weight of 200g / m 2 The single-layer polyester fabric is impregnated with antistatic finishing liquid at a bath ratio of 30:1, impregnated at 50°C for 50 minutes, and rolled twice, with a rolling rate of 94%. After the impregnation, it is dried at 90°C for 3 minutes and baked at 150°C for 2 minutes to obtain a surface layer fabric and an inner layer fabric respectively.

[0102] Wherein, the polyester fiber is prepared by the following steps:

[0103] The polyester chips and the normal pressure dyeable polyester masterbatch were mixed in a twin-screw extruder at a mass ratio of 100:30, and melt-extruded through a twin-screw melt spinning machine at a temperature of 275°C in the first zone, 280°C in the second zone, 290°C in the third zone, and 290°C in the fourth zone, and spun at a spinning speed of 1000 m / min, cooled, and drawn at a drawing multiple of 3.6 times to obtain a polyester fiber with a linear density of 180 dtex;

[0104] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning the layers, using polyester sewing thread as sewing thread, and sewing the surface fabric and the inner fabric through a multi-layer fabric quilting machine to obtain an anti-wrinkle and antistatic polyester fabric.

[0105] Comparative Example 1:

[0106] This comparative example discloses a method for preparing a double-layer polyester fabric, comprising the following steps:

[0107] Step (1), mixing a terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, a quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile in a mass ratio of 20:6.5:18:5:100:0.4, reacting at a speed of 180 r / min and a temperature of 70° C. for 8 hours, cooling to room temperature after the reaction, and removing the solvent ethanol by rotary evaporation at a temperature of 60° C. to obtain a reaction product, adding toluene 5 times the mass of the reaction product for washing, and drying at a temperature of 80° C. for 30 hours to obtain an antistatic agent; mixing the antistatic agent with water in a mass ratio of 1:25 to obtain an antistatic finishing liquid;

[0108] The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps:

[0109] S11, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was mixed with 50 wt% ethanol aqueous solution, 1 mol / L hydrogen chloride aqueous solution was added dropwise to adjust the pH value to 4, nanosilver was added, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50 wt% ethanol aqueous solution and nanosilver was 0.8:200:10, and the reaction was carried out at 45°C for 5 hours. After the reaction was completed, the filter cake was taken out by suction, 6 times the mass of ethanol of the filter cake was added for washing, and the nanosilver was dried at 50°C for 26 hours to obtain epoxidized nanosilver;

[0110] S12, dissolving the terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide, adding p-toluenesulfonic acid, dripping acrylic acid at 100°C for 2 hours, reacting at 100°C for 5 hours in a nitrogen atmosphere after the addition is complete, cooling after the reaction is complete, adding boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver, and continuing the reaction at 45°C for 28 hours, and after the reaction is complete, removing the solvent N,N-dimethylformamide by rotary evaporation at 100°C to obtain a terminal olefin-modified hyperbranched polyester / nanosilver composite material;

[0111] The mass ratio of the terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride ethyl etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 21:100:1:2.8:1.2:9:15;

[0112] The quaternary ammonium salt surfactant is prepared by the following steps:

[0113] Dimethylaminoethyl methacrylate and acetone were mixed uniformly at a mass ratio of 1:40, 1,12-dibromododecane was added dropwise, the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane was 2.1:1, the dropping time was 20 min, after the dropping was completed, the reaction was carried out at a set temperature of 60°C for 10 h, after the reaction was completed, the filter cake was taken out by suction, ethanol 8 times the mass of the filter cake was added for recrystallization three times, and the mixture was dried at 50°C for 24 h to obtain a quaternary ammonium surfactant;

[0114] Step (2), spinning polyester fiber into yarn as warp and weft yarn, the yarn count is 40S in British standard, weaving, and obtaining a gram weight of 180 g / m 2 The single-layer polyester fabric is impregnated with an antistatic finishing liquid at a bath ratio of 20:1, and is impregnated at 40°C for 60 minutes, and is double-impregnated and double-rolled, with a rolling rate of 88%. After the impregnation, the fabric is dried at 80°C for 5 minutes, and baked at 140°C for 3 minutes to obtain a surface layer fabric and an inner layer fabric, respectively.

[0115] Wherein, the polyester fiber is prepared by the following steps:

[0116] The polyester chips and the normal pressure dyeable polyester masterbatch were mixed in a twin-screw extruder at a mass ratio of 100:26, and melt-extruded through a twin-screw melt spinning machine at a temperature of 265°C in the first zone, 275°C in the second zone, 278°C in the third zone, and 280°C in the fourth zone. The spinning was carried out at a spinning speed of 800 m / min, and the spinning was carried out, followed by cooling and drawing at a drawing multiple of 3 times to obtain a polyester fiber with a linear density of 200 dtex.

[0117] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning the layers, using polyester sewing thread as sewing thread, and sewing the surface fabric and the inner fabric through a multi-layer fabric quilting machine to obtain a double-layer polyester fabric.

[0118] Comparative Example 2:

[0119] This comparative example discloses a method for preparing a double-layer polyester fabric, comprising the following steps:

[0120] Step (1), mixing nanosilver, hydroxyethyl methacrylate, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile in a mass ratio of 10:6.5:23:100:0.4, reacting at a speed of 180 r / min and a temperature of 70° C. for 8 hours, cooling to room temperature after the reaction, and removing the solvent ethanol by rotary evaporation at a temperature of 60° C. to obtain a reaction product, adding toluene 5 times the mass of the reaction product for washing, and drying at a temperature of 80° C. for 30 hours to obtain an antistatic agent; mixing the antistatic agent with water in a mass ratio of 1:25 to obtain an antistatic finishing liquid;

[0121] Step (2), spinning polyester fiber into yarn as warp and weft yarn, the yarn count is 40S in British standard, weaving, and obtaining a gram weight of 180 g / m 2 The single-layer polyester fabric is impregnated with an antistatic finishing liquid at a bath ratio of 20:1, and is impregnated at 40°C for 60 minutes, and is double-impregnated and double-rolled, with a rolling rate of 88%. After the impregnation, the fabric is dried at 80°C for 5 minutes, and baked at 140°C for 3 minutes to obtain a surface layer fabric and an inner layer fabric, respectively.

[0122] Wherein, the polyester fiber is prepared by the following steps:

[0123] The polyester chips and the normal pressure dyeable polyester masterbatch were mixed in a twin-screw extruder at a mass ratio of 100:26, and melt-extruded through a twin-screw melt spinning machine at a temperature of 265°C in the first zone, 275°C in the second zone, 278°C in the third zone, and 280°C in the fourth zone. The spinning was carried out at a spinning speed of 800 m / min, and the spinning was carried out, followed by cooling and drawing at a drawing multiple of 3 times to obtain a polyester fiber with a linear density of 200 dtex.

[0124] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning the layers, using polyester sewing thread as sewing thread, and sewing the surface fabric and the inner fabric through a multi-layer fabric quilting machine to obtain a double-layer polyester fabric.

[0125] Comparative Example 3:

[0126] This comparative example discloses a method for preparing a double-layer polyester fabric, comprising the following steps:

[0127] Step (1), mixing a terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, a quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile in a mass ratio of 20:6.5:18:5:100:0.4, reacting at a speed of 180 r / min and a temperature of 70° C. for 8 hours, cooling to room temperature after the reaction, and removing the solvent ethanol by rotary evaporation at a temperature of 60° C. to obtain a reaction product, adding toluene 5 times the mass of the reaction product for washing, and drying at a temperature of 80° C. for 30 hours to obtain an antistatic agent; mixing the antistatic agent with water in a mass ratio of 1:25 to obtain an antistatic finishing liquid;

[0128] The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps:

[0129] S11, γ-(2,3-epoxypropoxy)propyltrimethoxysilane was mixed with 50 wt% ethanol aqueous solution, 1 mol / L hydrogen chloride aqueous solution was added dropwise to adjust the pH value to 4, nanosilver was added, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50 wt% ethanol aqueous solution and nanosilver was 0.8:200:10, and the reaction was carried out at 45°C for 5 hours. After the reaction was completed, the filter cake was taken out by suction, 6 times the mass of ethanol of the filter cake was added for washing, and the nanosilver was dried at 50°C for 26 hours to obtain epoxidized nanosilver;

[0130] S12, dissolving the terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide, adding p-toluenesulfonic acid, dripping acrylic acid at 100°C for 2 hours, reacting at 100°C for 5 hours in a nitrogen atmosphere after the addition is complete, cooling after the reaction is complete, adding boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver, and continuing the reaction at 45°C for 28 hours, and after the reaction is complete, removing the solvent N,N-dimethylformamide by rotary evaporation at 100°C to obtain a terminal olefin-modified hyperbranched polyester / nanosilver composite material;

[0131] The mass ratio of the terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride ethyl etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 21:100:1:2.8:1.2:9:15;

[0132] The quaternary ammonium salt surfactant is prepared by the following steps:

[0133] Dimethylaminoethyl methacrylate and acetone were mixed uniformly at a mass ratio of 1:40, 1,12-dibromododecane was added dropwise, the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane was 2.1:1, the dropping time was 20 min, after the dropping was completed, the reaction was carried out at a set temperature of 60°C for 10 h, after the reaction was completed, the filter cake was taken out by suction, ethanol 8 times the mass of the filter cake was added for recrystallization three times, and the mixture was dried at 50°C for 24 h to obtain a quaternary ammonium surfactant;

[0134] Step (2), spinning polyester fiber into yarn as warp and weft yarn, the yarn count is 40S in British standard, weaving, and obtaining a gram weight of 180 g / m 2 The single-layer polyester fabric is impregnated with an antistatic finishing liquid at a bath ratio of 20:1, and is impregnated at 40°C for 60 minutes, and is double-impregnated and double-rolled, with a rolling rate of 88%. After the impregnation, the fabric is dried at 80°C for 5 minutes, and baked at 140°C for 3 minutes to obtain a surface layer fabric and an inner layer fabric, respectively.

[0135] Wherein, the polyester fiber is prepared by the following steps:

[0136] The polyester chips were melt-extruded through a twin-screw melt spinning machine, with the temperatures of 265°C in the first zone, 275°C in the second zone, 278°C in the third zone, and 280°C in the fourth zone, and the spinning speed was 800 m / min, followed by cooling and drawing, with the drawing multiple being 3 times, to obtain polyester fibers with a linear density of 200 dtex;

[0137] Step (3), laminating the surface fabric and the inner fabric, stacking and aligning the layers, using polyester sewing thread as sewing thread, and sewing the surface fabric and the inner fabric through a multi-layer fabric quilting machine to obtain a double-layer polyester fabric.

[0138] In the above examples and comparative examples: hydroxyethyl methacrylate comes from Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS No.: 868-77-9; methoxy polyethylene glycol acrylate comes from Xi'an Qiyue Biotechnology Co., Ltd., product name mPEG-AC, molecular weight 1000; γ-(2,3-epoxypropoxy)propyltrimethoxysilane comes from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., CAS No.: 2530-83-8; nanosilver comes from Shanghai MacLean Biochemical Technology Co., Ltd., particle size 120nm; terminal hydroxyl hyperbranched polyester comes from Perstorp, product name hyperbranched polyester Boltorn H20, molecular weight is 2100g / mol; acrylic acid comes from Anhui Jinyueguan New Material Technology Co., Ltd., CAS number: 79-10-7; boron trifluoride etherate comes from Jinan Hongchuang Chemical Co., Ltd., CAS number: 109-63-7; 2,3-epoxypropyltrimethylammonium chloride comes from Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS number: 3033-77-0; dimethylaminoethyl methacrylate comes from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number: 2867-47-2; 1,12-dibromododecane comes from Shanghai MacLean Biochemical Technology Co., Ltd., CAS number: 3344-70-5; polyester chips are commercially available spinning grade chips; normal pressure dyeable polyester masterbatch comes from Shaoxing Xineng Textile Technology Co., Ltd., and the specification is normal pressure cationic dyeable polyester ECDP containing polyether hydrophilic segments and sulfonate anion groups.

[0139] Test example:

[0140] like Figure 3-Figure 5 As shown, the polyester fabrics prepared in the examples and comparative examples were subjected to performance tests, and the specific test results are shown in Table 1:

[0141] Table 1

[0142]

[0143] The tests of various indicators in Table 1 are based on the following standards: the wrinkle recovery angle is measured with reference to GB / T3819-1997 "Determination of crease recovery of textile fabrics - Recovery angle method"; the antibacterial rate is measured with reference to GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles - Part 3: Oscillation method", in which Escherichia coli is selected as the bacteria; the surface resistance is measured with reference to GB / T22042-2008 "Test method for surface resistivity of antistatic properties of clothing"; the static voltage half-life is measured with reference to GB / T12703 "Evaluation of electrostatic properties of textiles".

[0144] It can be seen from the test results in Table 1 that the polyester fabric prepared by the present invention has excellent antistatic performance, good antibacterial performance and good anti-wrinkle effect.

[0145] The invention prepares a quaternary ammonium salt type surfactant with a double quaternary ammonium salt cationic structure and a terminal olefin modified hyperbranched polyester / nano-silver composite material containing a quaternary ammonium salt structure and an acrylate group, and copolymerizes the two with a hydrophilic component hydroxyethyl methacrylate and a methoxy polyethylene glycol acrylate containing a polyether hydrophilic structure by using a carbon-carbon double bond under an initiator condition, and compounding the obtained antistatic agent with water to obtain an antistatic finishing liquid; wherein the quaternary ammonium salt cationic group in the antistatic agent and the hydrophilic component hydroxyethyl methacrylate and the methoxy polyethylene glycol acrylate containing a polyether hydrophilic structure synergistically improve the antistatic performance of polyester fabrics; and the quaternary ammonium salt group can synergistically improve the antibacterial performance of the polyester fabrics with the nano-silver;

[0146] Due to the addition of normal pressure dyeable polyester masterbatch, sulfonate anion groups are introduced into polyester fibers, which improves the moisture absorption and regain and antistatic properties of polyester fabrics. In the antistatic finishing solution, the antistatic agent contains ester groups and quaternary ammonium salt cationic groups. During the padding process, the ester groups can produce eutectics with the polyester fibers based on the principle of similar compatibility. Ionic crosslinking occurs between the quaternary ammonium salt cationic groups and the sulfonate anion groups in the polyester fabric to form ionic bonds, which strengthens the interaction between the fiber molecular chains in the polyester fabric, which not only improves the wash resistance of the polyester fabric, but also because the antistatic agent is deposited between the fibers of the polyester fabric using ionic bonds, it limits the deformation and movement of the polyester fibers and improves the wrinkle resistance of the polyester fabric.

[0147] In the antistatic agent of Comparative Example 1, no terminal olefin-modified hyperbranched polyester / nanosilver composite material is added, the antistatic agent lacks inorganic antibacterial agent nanosilver, and the content of quaternary ammonium salt groups is reduced, so the antistatic performance and antibacterial performance of Comparative Example 1 are not as good as those of the embodiment;

[0148] In Comparative Example 2, the nanosilver has no surface modification and no quaternary ammonium salt surfactant is added. The antistatic agent lacks quaternary ammonium salt cationic groups and cannot form ionic crosslinking with the anionic groups of the polyester fiber to form ionic bonds. Therefore, the antibacterial and antistatic properties of Comparative Example 2 are not as good as those of the embodiment, and the water washability is reduced.

[0149] In the preparation process of the polyester fiber in Comparative Example 3, no normal pressure dyeable polyester masterbatch was added. The polyester fabric lacked sulfonate anion groups and could not undergo ion crosslinking with the antistatic agent in the antistatic finishing liquid during padding. Therefore, the antistatic performance of Comparative Example 3 was not as good as that of the embodiment, and its water wash resistance was reduced.

[0150] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an anti-wrinkle and anti-static polyester fabric, characterized in that: The following steps are involved: Step (1), mixing terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile, reacting, cooling, rotary evaporating, washing, and drying after the reaction to obtain an antistatic agent; mixing the antistatic agent with water to obtain an antistatic finishing liquid; The terminal olefin modified hyperbranched polyester / nanosilver composite material is prepared by the following steps: The terminal hydroxyl hyperbranched polyester and N,N-dimethylformamide are mixed and dissolved, p-toluenesulfonic acid is added, acrylic acid is added dropwise, and after the addition is completed, the reaction is carried out. After the reaction is completed, the temperature is lowered, and boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride and epoxidized nanosilver are added, and the reaction is continued. After the reaction is completed, rotary evaporation is performed to obtain a terminal olefin modified hyperbranched polyester / nanosilver composite material; Step (2), spinning polyester fibers into yarns as warp yarns and weft yarns, weaving to obtain a single-layer polyester fabric; impregnating the single-layer polyester fabric with an antistatic finishing liquid, and after the impregnation, drying and baking to obtain a surface fabric and an inner fabric respectively; Step (3), compounding the surface layer fabric and the inner layer fabric to obtain an anti-wrinkle and antistatic polyester fabric.

2. The method for preparing a wrinkle-resistant and antistatic polyester fabric according to claim 1, characterized in that: In the step (1), the mass ratio of the terminal olefin modified hyperbranched polyester / nanosilver composite material, hydroxyethyl methacrylate, quaternary ammonium salt surfactant, methoxy polyethylene glycol acrylate, ethanol, and azobisisobutyronitrile is 20-25:6.5-7:18-20:5-6:100-120:0.4-0.5; the reaction conditions are: reaction at a speed of 180-230 r / min and a temperature of 70-80° C. for 6-8 hours; and the mass ratio of the antistatic agent to water is 1:20-25.

3. The method for preparing a wrinkle-resistant and antistatic polyester fabric according to claim 1, characterized in that: The quaternary ammonium salt surfactant in step (1) is prepared by the following steps: Dimethylaminoethyl methacrylate and acetone are uniformly mixed, 1,12-dibromododecane is added dropwise, and after the addition is completed, the mixture is reacted. After the reaction is completed, the mixture is filtered, recrystallized, and dried to obtain a quaternary ammonium salt surfactant.

4. The method for preparing a wrinkle-resistant and antistatic polyester fabric according to claim 3, characterized in that: When preparing the quaternary ammonium salt surfactant in step (1), the molar ratio of dimethylaminoethyl methacrylate to 1,12-dibromododecane is 2.1-2.4:1; the dripping time of 1,12-dibromododecane is 20-30 minutes; and the reaction conditions are: reacting at a set temperature of 60-70° C. for 8-10 hours.

5. The method for preparing a wrinkle-resistant and antistatic polyester fabric according to claim 1, characterized in that: When preparing the terminal olefin modified hyperbranched polyester / nanosilver composite material in step (1), the epoxidized nanosilver is prepared by the following steps: Mixing γ-(2,3-epoxypropoxy)propyltrimethoxysilane with an ethanol aqueous solution, adding a regulator to adjust the pH value, adding nanosilver, reacting, and after the reaction is completed, filtering, washing, and drying to obtain epoxidized nanosilver; The mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 50wt% ethanol aqueous solution and nanosilver is 0.8-1:200-220:10, and the ethanol aqueous solution is 50wt% ethanol aqueous solution; the reaction conditions are: reacting at a pH value of 4-5 and a temperature of 45-55°C for 4-5h.

6. The method for preparing a wrinkle-resistant and antistatic polyester fabric according to claim 1, characterized in that: When preparing the terminal olefin modified hyperbranched polyester / nanosilver composite material in step (1), the mass ratio of terminal hydroxyl hyperbranched polyester, N,N-dimethylformamide, p-toluenesulfonic acid, acrylic acid, boron trifluoride etherate, 2,3-epoxypropyltrimethylammonium chloride, and epoxidized nanosilver is 21-25:100-120:1-1.1:2.8-3:1.2-1.5:9-11:15-18; the dripping condition of acrylic acid is: dripping at a temperature of 100-110° C. for 1.5-2 h; the reaction condition is: reacting at a temperature of 100-105° C. for 4-5 h in a nitrogen atmosphere; and the continued reaction condition is: continuing the reaction at a temperature of 45-55° C. for 24-28 h.

7. The method for preparing a wrinkle-resistant and antistatic polyester fabric according to claim 1, characterized in that: In the step (2), the yarn counts of the warp and weft yarns are both 40-60S in British standard; the weight of the single-layer polyester fabric is 180-200 g / m 2 .

8. The method for preparing a wrinkle-resistant and antistatic polyester fabric according to claim 1, characterized in that: In the step (2), the dipping operation includes: dipping at 40-50°C for 50-60 minutes, a bath ratio of 20-30:1, two dippings and two rollings, and a rolling rate of 88-94%; the drying conditions are: drying at 80-90°C for 3-5 minutes; and the baking conditions are: baking at 140-150°C for 2-3 minutes.

9. The method for preparing a wrinkle-resistant and antistatic polyester fabric according to claim 1, characterized in that: The polyester fiber in step (2) is prepared by the following steps: The polyester chips are mixed with the normal pressure dyeable polyester masterbatch, melt extruded, spun, cooled, and drawn to obtain polyester fibers; Among them, the mass ratio of polyester chips to normal pressure dyeable polyester masterbatch is 100:26-30; the conditions for melt extrusion are: melt extrusion through a twin-screw melt spinning machine, the temperature is 265-275°C in zone one, 275-280°C in zone two, 278-290°C in zone three, and 280-290°C in zone four; the spinning speed is 800-1000m / min; the drafting multiple is 3-3.6 times; the linear density of the polyester fiber is 180-200dtex.

10. An anti-wrinkle and anti-static polyester fabric prepared by the method for preparing an anti-wrinkle and anti-static polyester fabric as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Antistatic anti-wrinkle fabric

    CN108943901A

  • Preparation method of nano-silver coating of chitosan modified fabric

    CN105200773A

  • Soft and smooth woven fabric and application thereof in high-end women's wear

    CN109610167A